Kinetics and Mechanism of Rh(III) Catalyzed Oxidation of Fumaric Acid by Ce(IV) in Acidic Medium - Singh, R.A.; Singh, Anju (Asian Journal of Chemistry, 2010)
The kinetics of Rh(III) catalysed oxidation of fumaric acid by Ce(IV) has been investigated in acidic medium. The reaction shows first order kinetics with respect to fumaric acid, Ce(IV) and Rh(III) and no effect of the medium. There is no significant effect of ionic strength and potassium chloride on reaction rate. Elevation of temperature increases the rate of reaction. A mechanism consistent with the above kinetic results has been suggested.